Methods of Pre-Trial Investigation of Criminal Offenses and Content of Its Structural Elements: Case of Kazakhstan - Seidanov, A.B.; Utebaev, E.K.; Temirgazin, R.Kh.; Sydykova, A.E.; Zhuravlev, A.N. (International Journal of Criminology and Sociology, 2022)
Rationale for research is presented in the form of a proposed structure of the methodology’s elements for pre-trial investigation of criminal offenses. It is notable that this novelty is based on the provisions of the new edition of Criminal Code and Criminal Procedure Code of the Republic of Kazakhstan, which came into force on January 01, 2015. The research objective is to enhance the efficiency of investigating criminal offenses against the foundations of the constitutional order as well as the security of the state, criminal offenses in the field of informatization and communications, criminal offenses in the field of economic activity and medical criminal offenses, which, in turn, are the sources of the development of the structure of the methodology for pre-trial investigation of such types of socially dangerous acts. They were previously not covered in public editions. Research methods are the formation of the data structure of particular methods of pre-trial investigation of crimes based on not just theoretical experience, but also the accumulated practice of a preliminary investigation in the country, the new and far abroad, for example, crimes against the person, property, etc. Research results include the developed structure of the methodology for pre-trial investigation of these crimes. The study will serve as an impetus for further theoretical development of particular methods of pre-trial investigation of certain types of criminal offenses along with their implementation in the practice of pre-trial investigation in the country’s investigative apparatus.